The relationship between coaching leadership style and team cohesion of male and female athletes in team and individual selected disciplines - Sarpira, M.; Khodayari, A. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The present study aims to review the relationship between coaching leadership style and Team cohesion. Method and Subjects: The subjects of the study were all the elite athletes of team and individual disciplines in Tabriz in 2011 that would be sent to the provincial championships. 250 athletes were randomly selected. The instruments for the research were: standard leadership scale for sport questionnaire (LSS) and Team cohesion questionnaire (TCQ). The questionnaires were reviewed and their validities were approved by 15 academic experts and professors. Using Cronbach`s alpha coefficient, the researchers calculated the reliabilities of 95%, 90% respectively. This study is a descriptive -correlative one which is performed using field study method. Descriptive-Statistical method was used to present the information in tables and graphs and inferential statistical method (Spearman Correlation) was used to determine the relationship between coaching styles and Team cohesion and finally Mann-Whitney U test method was utilized to statistical comparison between coaches and male and female athletes in team and individual sports. Results and Discussion: The results showed that there was a clear and significant positive relationship between all aspects of team cohesion and training and practice leadership, task-oriented leadership, and relationship-oriented leadership styles. But there is no significant positive relationship between team cohesion dimensions and directive leadership style. The behavior of coaches in leadership style has a determining role in team cohesion, so coaches can improve the team cohesion by choosing an appropriate leadership style which consequently leads to success of athletes and achievement in competitions.